2008
DOI: 10.2337/dc08-0138
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Glycemic Control, and Risk of Hospitalization With Pneumonia

Abstract: OBJECTIVE -To examine whether diabetes is a risk factor for hospitalization with pneumonia and to assess the impact of A1C level on such risk. RESEARCH DESIGN AND METHODS-In this population-based, case-control study we identified patients with a first-time pneumonia-related hospitalization between 1997 and 2005, using health care databases in northern Denmark. For each case, 10 sex-and age-matched population control subjects were selected from Denmark's Civil Registration System. We used conditional logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
250
2
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(287 citation statements)
references
References 20 publications
20
250
2
15
Order By: Relevance
“…Studies have shown that obesity leads to impaired immune and lung function 47 , 48 , 49 . Obesity is also a risk factor for conditions that, in turn, increase risk of severe respiratory infection or severe outcomes, for example, hyperglycemia, obstructive sleep apnea, and aspiration associated with gastroesophageal reflux disease 50 , 51 , 52 . An association between obesity and influenza‐related hospitalizations may also be attributed to the increased risk of cardiovascular events following influenza infection 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that obesity leads to impaired immune and lung function 47 , 48 , 49 . Obesity is also a risk factor for conditions that, in turn, increase risk of severe respiratory infection or severe outcomes, for example, hyperglycemia, obstructive sleep apnea, and aspiration associated with gastroesophageal reflux disease 50 , 51 , 52 . An association between obesity and influenza‐related hospitalizations may also be attributed to the increased risk of cardiovascular events following influenza infection 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of 2 studies contradict this finding. In a large population-based case-control study 19 and a cohort study, 20 the risk of pneumonia-related hospitalizations and deaths was increased in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although single casual glucose levels of <11.1 mmol/l are within the 'normal' range [19], previous studies suggest that casual glucose levels >6.1 mmol/l are associated with adverse outcomes in CAP patients [11,12]. Thus, as have others [11,14,20], we classified participants a priori according to admission glucose levels into four levels of dysglycaemia: 4.0 to <6.1 mmol/l; 6.1 to <7.8 mmol/l; 7.8 to <11.1 mmol/l; and 11.1 to 20.0 mmol/l. Participants with admission glucose levels greater than 20 mmol/l or less than 4 mmol/l [19] were excluded (n=538) as such extreme glucose levels would mandate urgent hospital management, resulting in data inexorably confounded by treatment modality (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In a case-control study from Denmark, increasing dysglycaemia in patients with diabetes was associated with an increasing risk of admission for CAP, although the effects in CAP patients without diabetes were not assessed [14]. In the only other study, also from Denmark, dysglycaemia on admission for pneumonia was a strong predictor of 30 day mortality in both patients with and without diabetes [11].…”
mentioning
confidence: 99%